2015
DOI: 10.1186/s12879-015-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen class I and class II alleles are associated with susceptibility and resistance in borderline leprosy patients from Southeast Brazil

Abstract: BackgroundEvidence suggests that human leukocyte antigen (HLA) alleles influence the host immune response against Mycobacterium leprae. However, the association between HLA alleles and borderline (B) leprosy has not been studied. The aim of this study was to determine whether HLA class I and II molecules are associated with susceptibility or resistance to B leprosy including borderline-tuberculoid (BT), borderline-borderline (BB), and borderline-lepromatous (BL).MethodsDNA was obtained by the salting-out techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The involvement of HLA complex in leprosy has been demonstrated immunologically and genetically, but genetic studies of HLA genes in borderline leprosy and leprosy reactions were rarely reported. de Souza-Santana et al (122) genotyped the HLA class I (A * , B * , and C * ) and class II (DRB1 * and DQB1 * ) loci in a cohort consisting of 202 borderline leprosy (BT, BB, BL) patients of which 94 had T1R and 478 healthy controls (122). Their results demonstrated that HLA-C * 05, HLA-DRB1 * 07, and HLA-DQB1 * 02 were genetically associated with borderline leprosy, while HLA-B * 15 showed a significantly high frequency in T1R (122).…”
Section: Genes Associated With Leprosy Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of HLA complex in leprosy has been demonstrated immunologically and genetically, but genetic studies of HLA genes in borderline leprosy and leprosy reactions were rarely reported. de Souza-Santana et al (122) genotyped the HLA class I (A * , B * , and C * ) and class II (DRB1 * and DQB1 * ) loci in a cohort consisting of 202 borderline leprosy (BT, BB, BL) patients of which 94 had T1R and 478 healthy controls (122). Their results demonstrated that HLA-C * 05, HLA-DRB1 * 07, and HLA-DQB1 * 02 were genetically associated with borderline leprosy, while HLA-B * 15 showed a significantly high frequency in T1R (122).…”
Section: Genes Associated With Leprosy Reactionsmentioning
confidence: 99%
“…de Souza-Santana et al (122) genotyped the HLA class I (A * , B * , and C * ) and class II (DRB1 * and DQB1 * ) loci in a cohort consisting of 202 borderline leprosy (BT, BB, BL) patients of which 94 had T1R and 478 healthy controls (122). Their results demonstrated that HLA-C * 05, HLA-DRB1 * 07, and HLA-DQB1 * 02 were genetically associated with borderline leprosy, while HLA-B * 15 showed a significantly high frequency in T1R (122). Since the association between HLA and T1R is rarely reported in the literature, these results need further confirmation in different populations.…”
Section: Genes Associated With Leprosy Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of outcomes following M. leprae infection is determined by host factors (van Hooij et al 2019) ranging from anti-inflammatory T helper-2 (Th2)-mediated immunity against high bacterial loads and antibodies against M. leprae antigens in MB leprosy to strong pro-inflammatory T helper-1 (Th1) and T helper-17 (Th17)-mediated immunity characteristic of PB leprosy (Saini et al 2013). The human leukocyte antigen (HLA) alleles are also hypothesized to influence host immune responses against M. leprae infection (de Souza-Santana et al 2015). Thus, a reliable diagnostic test for leprosy should be able to capture the different clinical outcomes of M. leprae infection, including both cellular and humoral markers (van Hooij et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Functional assays have demonstrated that HLA‐DR, ‐DP, and ‐DQ are involved in the restricted recognition of M. leprae antigens by human TH1 and regulatory lymphocytes (Mutis et al., ). A large number of family‐ and population‐based association studies have shown an influence of HLA class I and II alleles towards susceptibility and protection to leprosy (Ottenhoff & de Vries, ; Geluk & Ottenhoff, ; Alcais et al., ; de Souza‐Santana et al., ). Although DR antigens seem to be important for the subtype of leprosy developed, their involvement in leprosy is still unclear.…”
Section: Introductionmentioning
confidence: 99%